DETERMINATION OF REGULARITIES PERTAINING TO FORCEFUL LOADING OF ELASTIC ELEMENT OF SAWING SECTION - M. G. Kiselev; A. V. Drozdov; D. A. Yamnaya (Наука и техника)
The paper proposes additionally to transmit bidimensional periodic circulation motion to a blanket occurring in the sawing plane surface with the purpose to intensify the sawing process of diamond mono-crystals with simultaneous quality improvement of sawed semi-finished products. An industrial sawing section modernization of the ШП-2-machine tool has been carried out in accordance with the above-mentioned approach. The purpose of the paper is an experimental determination of force value which is exerted on elastic washer by boom support screws in relation to conditions and excitation mode of a vibrating system of the modernized sawing section. The obtained data make it possible to determine optimal excitation parameters of forced vibrations.